Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana - Yin, Zi-Wei (Zootaxa, 2019)
Two new species of the Neotropical pselaphine genus Batoctenus Sharp, 1887 are described from French Guiana, i.e., B. kawmontis sp. nov., and B. kociani sp. nov., with their habitus and major diagnostic characters illustrated.